2020
DOI: 10.5194/tc-2020-217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive diffusion of climate signals recorded in ice-vein ionic impurities

Abstract: Abstract. A theory of vein impurity transport conceived two decades ago predicts that signals in the bulk concentration of soluble ions in ice migrate under a temperature gradient. If valid, it would mean that some palaeoclimatic signals deep in ice cores (signals from vein impurities as opposed to matrix/grain-boundary impurities) suffer displacements that upset their dating and alignment with other proxies. We revisit the vein physical interactions to show that a strong diffusion prevents such signals from s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As ice grains grow in size, especially in deep ice, they can either displace impurities which are subsequently preferentially located at the grain boundaries, or experience drag by inclusions of insoluble impurities (Stoll, Eichler, Hörhold, Shigeyama, & Weikusat, 2021 and references within). On the one hand, especially soluble species are affected by the diffusion along the network of ice veins, which can cause possible post‐depositional alteration of ice core paleoclimate records (Ng, 2021; Rempel et al., 2001). On the other hand, post‐depositional change has also been documented for insoluble impurities related to dust deposition.…”
Section: Introductionmentioning
confidence: 99%
“…As ice grains grow in size, especially in deep ice, they can either displace impurities which are subsequently preferentially located at the grain boundaries, or experience drag by inclusions of insoluble impurities (Stoll, Eichler, Hörhold, Shigeyama, & Weikusat, 2021 and references within). On the one hand, especially soluble species are affected by the diffusion along the network of ice veins, which can cause possible post‐depositional alteration of ice core paleoclimate records (Ng, 2021; Rempel et al., 2001). On the other hand, post‐depositional change has also been documented for insoluble impurities related to dust deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The latter represents the active fluctuations of the system, such as those originating in particular processes described in [60][61][62][63]. Nutrient sources, such as dissolved silica, oxygen, nitrogen and methane, play a vital role in the life of ice-bound micro-organisms, such as algae and bacteria [64][65][66][67][68][69][70]. Here we assume that Dch > Da , consistent with [71][72][73][74], and Dch > D(z).…”
Section: Methodsmentioning
confidence: 99%
“…The modeling of diffusion of sulfate (e.g. Rempel et al, 2001;2002;B03;Ng et al, 2021) has focused on sulfate in a vein network. However, the location of sulfate is not well established and will affect the ability for sulfate to diffuse.…”
Section: Deep Ice Older Than 450 Kamentioning
confidence: 99%
“…Addressing the diffusion of sulphate in veins, Rempel et al (2001) showed that impurity fluctuations may retain their amplitude but migrate towards warmer temperatures and away from the ice the impurity was deposited with; however, Ng (2021) showed that including the Gibbs-Thompson effect due to the grain curvature may cause these peaks to diffuse rapidly and therefore not retain their amplitude nor migrate. The sulfate and electrical conductivity measurements (ECM) of Antarctic ice cores also show reduced amplitude (Barnes et al, 2003, hereafter B03;Fujita et al, 2015;Fudge et al, 2016) in older ice.…”
Section: Introductionmentioning
confidence: 99%